“Respuesta del cultivo de maíz dulce (Zea mays L.) a la fertilización con diferentes abonos orgánicos, en la zona de Babahoyo”. - Aguirre Icaza, Juan Carlos (2017)
VII. SUMMARY The present experimental work was developed in the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7.5 of the road to Babahoyo - Montalvo. The geographic coordinates are 277438.26 UTM of longitude west and 110597.97 UTM south latitude and a height of 8 msnm. The soil is clay loam, drainage and regular topography. The sweet corn Bandit F1 was used as seed material. The studied treatments consisted of organic, edaphic and foliar fertilizers with their respective doses, which were T1 (Lombricompost 1,500 kg + Activa 1,0 L + Alganova 300 gr); T2 (Lombricompost 1.000 kg + Activa 1.0 L + Alganova 300 gr); T3 (Lombricompost 2,000 kg + Activa 1,0 L + Alganova 300 gr); T4 (Ihumix DG 50 kg + Active 1.0 L + Alganova 300 gr); T5 (Ihumix DG 40 kg + Activa 1.0 L + Alganova 300 gr), T6 (Ihumix DG 60 kg + Activa 1.0 L + Alganova 300 gr) and T7 (140 kg N, 80 kg P, 90 kg K) . The design of Complete Blocks at Random was used, with seven treatments and three repetitions. The comparison of the averages was made with the Duncan test at 95% probability. During the development of the experiment the tasks of Preparation of the land, Sowing, Control of weeds, Irrigation, Fertilization, Control of pests and diseases and Harvest were carried out. To estimate the effects of the treatments, the data of plant height, length and diameter of the ear, number of grains per ear, weight of 1000 grains, yield and economic analysis were taken. Based on the results, it was determined that the applied organic fertilizers had influential effects on the agronomic characteristics of the sweet corn (Zea mays L.) crop in the Babahoyo area; in the agronomic characteristics of plant height, length and diameter of ear, number of grains per ear and weight of 1000 grains, higher averages were registered applying 140 kg N; 80 kg P, 90 kg K and the application of Lombricompost 2000 kg + Activa 1,0 L + Alganova 300 gr allowed to have higher yield and net profit with $ 210,10. Keywords: sweet corn, fertilization, organic fertilizers, worm compost, active, Alganova, Ihumix DG, Nitrogen, Phosphorus, Potassium.